Comparison of short‐course versus long‐course antibiotic treatment for community‐acquired pneumonia: a meta-analysis of randomized control trials - Khowaja, Rahil; Karimi, Fazila (International Journal Of Community Medicine And Public Health, 2023)
The duration of antibiotic treatment of community acquired pneumonia (CAP) has been a topic of discussion in scientific communities because of the lack of evidence about the current regimen, i.e., 7 to 10 days of treatment. The present meta-analysis aims to compare the effectiveness of shorter-duration antibiotic treatment with longer-duration antibiotic treatment in patients with CAP. This meta-analysis was conducted and reported in accordance with the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) statement. Two authors carried out a scientific literature search on online databases, including EMBASE, PubMed and Cochrane Library. The following keywords or corresponding medical subject headings (MeSH) were used for the search of relevant articles: “community-acquired pneumonia”, “antibiotics”, “drug therapy”, “short course”, “long course”, and "duration". The primary outcomes assessed in this meta-analysis were clinical efficacy, microbiological efficacy and radiological resolution, other outcomes included mortality and drug related adverse events. Total 6 RCTs were included in the current meta-analysis. No significant differences were found between shorter-course and longer-course antibiotic treatment in terms of clinical efficacy, microbiological efficiency, radiological resolution, mortality and drug-related adverse events. The findings of the present meta-analysis showed that the treatment of CAP with a shorter course of antibiotic is as effective as a longer course of therapy.